Implementasi Metode Pembelajaran Kolaboratif Pada Kurikulum Merdeka Kelas X MA Tarbiyatul Islamiyah Batangan - Hilmi, Ro'fat; Aliyah, Himmatul; Ana, Nilna Syifa; Ismawarni, Ismawarni (AL-BURHAN, 2024)
The purpose of this study is to explain the steps and impacts of collaborative learning on the independent curriculum for class X MA Tarbiyatul Islamiyah Batangan. The type of qualitative research with data collection using interviews, observations, and documentation. Research Results The steps include 1) Teachers create teaching modules and implement opening, core and closing activities, 2) attend training, 3) provide modern learning media. Collaborative Learning has both positive and negative impacts. The positive impacts are 1) Student activity increases. 2) Learning becomes more interactive and is able to produce better learning outcomes. 3) Environmental factors must support the learning process to create good, safe, and comfortable conditions. While the negative impacts of collaborative learning are 1) it takes a long time to set up the class 2) for quiet students, teachers must pay more attention so that students remain comfortable in learning, 3) there is dominance of several students.Keywords: Implementation, Independent Curriculum, Collaborative Learning